2019
DOI: 10.1111/nph.16220
|View full text |Cite
|
Sign up to set email alerts
|

Linkage‐linkage disequilibrium dissection of the epigenetic quantitative trait loci (epiQTLs) underlying growth and wood properties in Populus

Abstract: Increasing evidence indicates that DNA methylation is heritable and serves as an essential marker contributing to phenotypic variation. Linkage‐linkage disequilibrium mapping was used to decipher the epigenetic architecture underlying nine growth and wood property traits in a linkage population (550 F1 progeny) and a natural population (435 unrelated individuals) of Populus using methylation‐sensitive amplification polymorphism (MSAP)‐based analysis. The interactions between genetic and epigenetic variants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…This includes research on life history stages, climate (i.e., experiments covering wider geographical locations), and other environmental conditions (e.g., soil conditions; [67]). The epigenetic effects on genotypes might also be important for the growth response observed in the present study [68,69]. Additionally, because our study was conducted using local varieties from the Kyushu region, additional studies capturing wider genetic variation (e.g., populations from natural forests) with different approaches-such as genome-wide association study (GWAS)-are necessary to generalize the findings of this study.…”
Section: Discussionmentioning
confidence: 93%
“…This includes research on life history stages, climate (i.e., experiments covering wider geographical locations), and other environmental conditions (e.g., soil conditions; [67]). The epigenetic effects on genotypes might also be important for the growth response observed in the present study [68,69]. Additionally, because our study was conducted using local varieties from the Kyushu region, additional studies capturing wider genetic variation (e.g., populations from natural forests) with different approaches-such as genome-wide association study (GWAS)-are necessary to generalize the findings of this study.…”
Section: Discussionmentioning
confidence: 93%
“…We compared our GWAS results with previous GWAS studies for similar traits in P. trichocarpa (Wegrzyn et al, 2010;Porth et al, 2013a;Porth et al, 2013b;Evans et al, 2014;McKown et al, 2014b;Chhetri et al, 2019) and other Populus species including P. deltoides (Fahrenkrog et al, 2017), P. euphratica (Ma et al, 2013;Jia et al, 2020) and P. tomentosa (Quan et al, 2016;Chen B. et al, 2018;Quan et al, 2019;Lu et al, 2020). We found very minimal overlap in the genes and/or gene families detected.…”
Section: Comparison With Previous Studiesmentioning
confidence: 84%
“…Jia et al (2020) identified 82 genes related to seed salinity tolerance in P. euphratica, including a zinc finger protein similar to one that we detected for leaf abaxial density that regulates gas exchange in plants. Lu et al (2020) identified 23 genes involved in three growth and six wood property traits and Quan et al (2019) identified 203 lignin biosynthetic genes, 81 TF genes, 36 microRNAs and 71 long non-coding RNA genes for 10 growth and wood property traits in the same P. tomentosa population. However, these studies have no apparent overlap in gene functions for similar morphology or wood property traits in our study.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…To overcome limitations, integrated genetic mapping by combining linkage and linkage-disequilibrium is recommended. Recently, an integrated linkage and linkage-disequilibrium mapping was conducted for the identification of epiQTLs in plants [89]. Using 550 F1s and 435 natural germplasm accessions a huge number of epiQTLs (163 epiQTLs) were found to be associated with growth and wood properties in Populus.…”
Section: Epiqtls and Epigenome-wide Association Study (Ewas)mentioning
confidence: 99%
“…Using 550 F1s and 435 natural germplasm accessions a huge number of epiQTLs (163 epiQTLs) were found to be associated with growth and wood properties in Populus. Further, 23 causal genes present within epiQTL regions showed cause and effect relationship as revealed by the coregulation of eQTN (expression quantitative trait nucleotide) and eQTM (expression quantitative trait methylation) [89].…”
Section: Epiqtls and Epigenome-wide Association Study (Ewas)mentioning
confidence: 99%